To use indwelling drainage or not in dual-plane breast augmentation mammoplasty patients: A comparative study. Issue 29 (17th July 2020) - Xiao, Yiding; Hu, Jianqiang; Zhang, Mingzi; Zhang, Wenchao; Qin, Feng; Zeng, Ang; Wang, Xiaojun; Liu, Zhifei; Zhu, Lin; Yu, Nanze; Si, Loubin; Long, Fei; et al.
Abstract : Abstract: To explore the necessity of indwelling drainage in dual-plane breast augmentation mammoplasty patients. Female patients (123 in total) were selected from June 2015 to June 2018 in the Department of Plastic Surgery at Peking Union Medical College Hospital and were randomly divided into 2 different groups: the with drainage group (WD group, 57 patients) and the without drainage group (WOD group, 66 patients). In the 2 groups, the operation time, postoperative stay, and hospitalization expenses were recorded. The BREAST-Q Version 2.0 Augmentation Module Pre- and Postoperative Scales (Chinese Version) were used to evaluate psychosocial well-being, sexual well-being, physical well-being, and satisfaction with breasts preoperatively and postoperatively (1 year after operation). Before the operation, no significant differences were found in psychosocial well-being, sexual well-being, physical well-being, or satisfaction with breasts between these 2 groups. In the WOD group, postoperative stay and hospitalization expenses were remarkably decreased, but the operation time was similar, compared with the WD group. Compared with before the operation, both groups had significantly increased scores in psychosocial well-being, sexual well-being, and satisfaction with breasts after the operation. However, no significant differences were found between the 2 groups. No complications were found in any of the patients. Although the operation time was not significantly decreased, patients without drainage could save much more time and money and simultaneously reach similar postoperative effects in psychosocial well-being, sexual well-being, physical well-being, and satisfaction with breasts. Therefore, drainage may not be necessary in patients who undergo dual-plane breast augmentation mammoplasty.